Fatigue in Patients with Parkinson’s Disease - Kazuo Abe; Mayako Takanashi; Takehiko Yanagihara (Behavioural Neurology)
Purpose: Fatigue is a complaint frequently encountered among patients with Parkinson’s disease (PD), however, the pathophysiological mechanism remains unclear. Methods: We evaluated fatigue in 26 patients clinically diagnosed to have PD (16 men, 10 women) and age- and sex- matched 26 controls (16 men, 10 women) without neurological deficits by using a fatigue scale. In addition to neurological and neuropsychological examinations, all patients underwent MRI and SPECT using 99mTc-HMPAO. Results: Patients with PD had normal cognitive function as judged by the MMSE, but showed significantly high scores with the fatigue and depression scales in comparison to controls (p). There was no significant correlation between the depression scale and the fatigue scale, or between the degree of disability and the fatigue scale in patients with PD, although a significant correlation existed between the depression scale and the fatigue scale in controls. With SPECT, a significant correlation was found between the fatigue scale and the reduction of perfusion in the frontal lobe (p) in patients with PD. Conclusions: The present study suggested that sense of fatigue in patients with PD might be associated with frontal lobe dysfunction.